The Effect of Feature Selection on Music Genre Classification - Giri, I Nyoman Yusha Tresnatama; Putri, Luh Arida Ayu Rahning (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2021)
One of the things that affects classification results is the correlation of features to the class of a data. This research was conducted to determine the effect of the reduction of features (independent variable) that have the weakest correlation or have a distant relationship with the class (dependent variable). Bivariate Pearson Correlation is used as a feature selection method and K-Nearest Neighbor is used as a classification method. Results of the test showing that, 75.1% average accuracy was obtained for classification without feature selection, while using feature selection, average accuracy was obtained in the range of 75% - 79.3%. The average accuracy obtained by the selection of features tends to be higher compared to the accuracy obtained without selection of features.